Analysis of the implementation of the CDC (Centralized Document Collateral) credit file system at BTN Syariah Bandung through the PDCA cycle - Nendita Syalwa Nurfadillah; Sulton Sudrajat; Indi Siti Rahmawati; Rani Indriawati; Dian Rosinawati (Keynesia : International Journal of Economy and Business, 2024)
Bank BTN, in supporting KPR financing, requires customers to prepare several documents, including personal identity, financial information, and certificates of title to home/equipment/vehicle ownership guarantees. Efficient storage and management of these documents are crucial to prevent loss due to mismanagement. To enhance services, Bank BTN has implemented a Centralized Document Collateral (CDC) documentation system. This study aims to analyze the CDC system's implementation using the PDCA cycle to evaluate each work step. Employing a qualitative descriptive method, data were collected from credit processing units at Bank BTN Syariah Bandung through observations, interviews, and literature studies. The findings indicate that the CDC system significantly improves document management efficiency, with key benefits including reduced document loss, streamlined retrieval processes, and enhanced security measures. These improvements contribute to more effective work processes and higher service quality for customers. However, some obstacles were identified, such as limited technological infrastructure and storage capacity, which require follow-up actions to enhance performance. Solutions like increasing server capacity, adopting cloud storage, optimizing data management can address these issues. The study concludes that the CDC system is a valuable tool in documenting customer credit files at Bank BTN Syariah Bandung, offering substantial enhancements in operational effectiveness and document security.